Assessment of Ground Water Quality in Gajanan Colony, Ahmednagar. By Water Quality Index (WQI) - Patil Varsha Dilip; Mhaismale Sheetal Dnyaneshwar; Lonkar Dhanashri Rajendra; Nikam Priyanka Suresh (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A water quality analysis was carried out in Ahmednagar city. Different parameters were analyzed that are pH, alkalinity, turbidity, TDS, total hardness and chlorides. The sampling sites showed that the physicocmc al parameters were within the water quality standards and the quality of water was found to be fit for drinking.Water is an essential natural resource for sustaining life and environment but over the last few decades the water quality is deteriorating due to it’s over exploitation. Water quality is essential parameter to be studied when the overall focus is sustainable development keeping mankind at focal point. Groundwater is the major source of drinking water in rural as well as in urban areas and over 94% of the drinking water demand is met by groundwater.Assessment ground water quality is necessary as it controls it’s as usability for drinking purpose .The study was carried out by the physic-chemical and biological analysis of ground water quality.